2022
DOI: 10.1097/md.0000000000032132
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing network pharmacology and molecular docking to clarify Duhuo Jisheng decoction potential mechanism of osteoarthritis mitigation

Abstract: As a classic remedy for treating Osteoarthritis (OA), Duhuo Jisheng decoction has successfully treated countless patients. Nevertheless, its specific mechanism is unknown. This study explored the active constituents of Duhuo Jisheng decoction and the potential molecular mechanisms for treating OA using a Network Pharmacology approaches. Screening active components and corresponding targets of Duhuo parasite decoction by traditional Chinese medicine systems pharmacology database and analysis platform database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Our findings are similar to the relevant studies [ 48 , 49 ]. Network pharmacology approaches demonstrated that DHJSD could reduce the immune-inflammatory reaction, inhibit apoptosis of chondrocytes, strengthen proliferation and repair of chondrocytes and reduce the inflammatory response in a multi-component–multi-target–multi-pathway way to play a role in the treatment of KOA [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to the relevant studies [ 48 , 49 ]. Network pharmacology approaches demonstrated that DHJSD could reduce the immune-inflammatory reaction, inhibit apoptosis of chondrocytes, strengthen proliferation and repair of chondrocytes and reduce the inflammatory response in a multi-component–multi-target–multi-pathway way to play a role in the treatment of KOA [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%